2021
DOI: 10.3390/metabo11120874
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolic Profiles Based on Nuclear Magnetic Resonance Spectroscopy among Patients with Deep Vein Thrombosis and Healthy Controls

Abstract: Deep venous thrombosis (DVT) is associated with significant morbidity and mortality. Studies on changes in the level of metabolites could have the potential to reveal biomarkers that can assist in the early detection, diagnosis, monitoring of DVT progression, response to treatment, or recurrence of DVT. In this scenario, the metabolomic analysis can provide a better understanding of the biochemical dysregulations of thrombosis. Using an untargeted metabolomic approach through magnetic resonance spectroscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 45 publications
0
18
1
Order By: Relevance
“…21 Conversely, a study of serum metabolic profiles based on nuclear magnetic resonance spectroscopy in patients with deep vein thrombosis and healthy controls showed significant reductions in leucine, valine and alanine concentrations in the thrombosis group. 22 In view of the conclusions of the above studies and the heterogeneity of arterial and venous thrombosis, we inferred that these BCAAs are potential biomarkers of CVT.…”
Section: Discussionmentioning
confidence: 81%
“…21 Conversely, a study of serum metabolic profiles based on nuclear magnetic resonance spectroscopy in patients with deep vein thrombosis and healthy controls showed significant reductions in leucine, valine and alanine concentrations in the thrombosis group. 22 In view of the conclusions of the above studies and the heterogeneity of arterial and venous thrombosis, we inferred that these BCAAs are potential biomarkers of CVT.…”
Section: Discussionmentioning
confidence: 81%
“…Limited literature is available for comparison with the findings of the current study. Among the top 20 metabolites, only EPA and isoleucine have been reported to be associated with thrombosis 18 . However, contrary to an earlier report that EPA is linked to reduced risk of thrombosis, EPA was associated with increased risk of thrombosis in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang et al showed that the metabolite trimethylamine N-oxide (TMAO) was associated with future risk of atherosclerotic events, and they discovered a novel link between the gut-flora-dependent metabolism of dietary phosphatidylcholine and cardiovascular pathogenesis 13 . So far, few studies have used metabolomics technology to explore the etiology of thrombosis [14][15][16][17][18] , and no studies have used the platform to examine thrombosis after surgery in children with CHD. In this study, we aimed to identify novel metabolites and metabolic pathways that are associated with the development of thrombosis after cardiac surgery in children with CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies identified metabolomic biomarkers for neurodegenerative disorders, but human metabolomic studies of tinnitus are lacking. A study in rats identified perturbations in several metabolic pathways with tinnitus, and multiple metabolite alterations demonstrated in brain tissue were also demonstrated in plasma .…”
Section: Introductionmentioning
confidence: 99%